2014
DOI: 10.1089/thy.2013.0523
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab-Including Combined Modality Treatment for Primary Thyroid Lymphoma: An Effective Regimen for Elderly Patients

Abstract: Background: Primary thyroid lymphoma (PTL) develops mostly in middle-aged and older females. However, the optimal treatment for elderly patients with diffuse large B-cell lymphoma (DLBCL), which accounts for most PTL cases, is unclear. Rituximab is a promising drug that, in combination with traditional combination therapy, has demonstrated an increased antitumor effect without a substantial increase in toxicity. In this study, treatment outcomes of elderly patients with thyroid DLBCL who underwent rituximab-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 27 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…Moreover, rituximab was approved by the U.S. Food and Drug Administration in 2006 as a first-line drug for PTL, and most of the DLBCL and mixed MALT and DLBCL patients who were expected to have poor prognosis were eligible for a combination rituximab and CHOP treatment regimen in this study. The combination of rituximab with CHOP is associated with improved survival rates among elderly patients with B-cell lymphoma and is a promising treatment for elderly patients with PTL [ 17 18 ]. Secondly, the proportion of patients with MALT lymphoma, which has better prognosis than DLBCL, was greater in the present study (42.1%) than in previous studies in the literature, which reported rates ranging from 10.0% to 28.0% [ 1 6 7 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, rituximab was approved by the U.S. Food and Drug Administration in 2006 as a first-line drug for PTL, and most of the DLBCL and mixed MALT and DLBCL patients who were expected to have poor prognosis were eligible for a combination rituximab and CHOP treatment regimen in this study. The combination of rituximab with CHOP is associated with improved survival rates among elderly patients with B-cell lymphoma and is a promising treatment for elderly patients with PTL [ 17 18 ]. Secondly, the proportion of patients with MALT lymphoma, which has better prognosis than DLBCL, was greater in the present study (42.1%) than in previous studies in the literature, which reported rates ranging from 10.0% to 28.0% [ 1 6 7 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In case of aggressive histological subtype, such as DLBCL or a non‐localized indolent subtype, the PTL should be treated with both chemotherapy and RT …”
Section: Primary Thyroid Lymphoma: From Diagnosis To Treatmentmentioning
confidence: 99%
“…Dralle et al ( 15 ) suggested that rituximab could improve survival of patients with primary thyroid DLBCL. Watanabe et al ( 16 ) showed that the inclusion of rituximab to combination therapy was effective for elderly patients with primary thyroid DLBCL. These findings suggested that chemotherapy including rituximab in combination with supplementary radiotherapy may be optimal treatment modality for patients with primary thyroid DLBCL.…”
Section: Discussionmentioning
confidence: 99%